Rickets, BeriBeri, and Iron Deficiency: micronutrient deficiencies in children - Phillip W Erbele; Krista Erbele; Philip R. Fischer (Bhutan Health Journal, 2016)
Some “forgotten” micronutrient deficiencies continue to be common in children. Deficiencies of vitamin D and/or calcium can cause rickets, a crippling condition related to poor mineralization of growing bones. Rickets is diagnosed by identifying skeletal deformities, elevation of alkaline phosphatase levels, and abnormal epiphyses on x-ray. Treatment is with vitamin D and calcium. Prevention hinges on improving the daily intake of calcium, regular sun exposure, or dietary supplementation. Beriberi is due to thiamine deficiency. Infants with beriberi present in heart failure while older children present with neurological abnormalities. Treatment is with thiamine, and prevention requires alterations to improve dietary thiamine intake – by supplementing mothers of breastfed babies, increasing legume and unpolished rice intake, and diversifying diets. Iron deficiency continues to be a problem for nearly half of the world’s children. Bhutan has made strides to eliminate this problem through active de-worming programs and iron supplementation programs.